Pengaruh Brand Trust Dan Harga Terhadap Keputusan Penggunaan Jasa Pada Lembaga Kita Center Pekanbaru - Salsabila, Hana; Mandataris, Mandataris (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine the influence of Brand Trust and Price on Service Use Decisions at the Kita Center Pekanbaru Institution. The method used in this research is descriptive and quantitative statistics. The sample in this study amounted to 67 respondents using a purposive sampling technique. The measurement scale uses a Likert scale. From data analysis using multiple linear regression analysis and hypothesis testing using SPSS, the results show that brand trust partially has a positive and significant effect with tcount > ttable (5.310 > 1.997) and Sig value < ? (0.000 < 0.05), partial price positive and significant effect with tcount > ttable (5.361 > 1.997) and Sig value < ? (0.000 < 0.05). Based on the results of the simultaneous test, brand trust and price have a significant effect on the decision to use services with Fcount > Ftable (83.204 > 3.14) and the Sig value. < 0.05 (0.000 < 0.05).